Application of a phosphonium-based ionic liquid for reactive textile dye removal: Extraction study and toxicological evaluation. (15th February 2022) - Santos Klienchen Dalari, Beatriz Lima; Lisboa Giroletti, Cristiane; Malaret, Francisco J.; Skoronski, Everton; Hallett, Jason P.; Matias, William Gerson; Puerari, Rodrigo Costa; Nagel-Hassemer, Maria Eliza
Abstract: Textile dyeing processes are known for their negative environmental impacts due to the production of aqueous effluents containing toxic dyes. Therefore, new wastewater treatment processes need to be developed to treat such effluents, including Liquid-Liquid Extraction (LLE) process using Ionic Liquids (IL). This work aimed to evaluate the application of the hydrophobic IL trihexyltetradecylphosphonium decanoate to extract black, navy, and royal reactive dyes from water and evaluate the toxicological aspects of the resulting water stream. We investigated the effect of selected parameters, such as pH (2–12), temperature (20–50 °C), salt effects, dye concentration (0.5–50 mg/L), and phase volume ratio (900–9000) on the dye extraction. The results showed extraction yields as high as 97% for the three dyes and an extraction capacity of approximately 300 mg/g for black and navy dyes and 400 mg/g for royal. The toxicity tests involved Lactuca sativa, Triticum aestivium L, and Daphnia magna as bioindicators. The difference between the toxicity of the dye solutions before and after extraction was not statistically significant when L. sativa and Triticum aestivum L were used as bioindicators. However, the extracted solution showed increased toxicity towards D. magna due to traces of IL. Overall, the IL has a high extraction capacity for the black, navy, and royal dyes. Nevertheless, further studies on LLE associated with other processes must be carried out to reduce the risk linked to the toxicity of IL transferred to the water. Graphical abstract: Image 1 Highlights: We applied Trihexyltetradecylphosphonium decanoate to remove textile dyes in water. Effect of phase volume ratio, temperature, salt, and dye concentration was studied. The phosphonium-based IL showed an impressive extraction capacity of 620 mg/g. Extractions were succeeded (>97%) and did not affect the phytotoxicity of water. Phosphonium-base IL has the potential for dye extraction from textile wastewater.